Preoperative Fluorine 18 Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography for Prediction of Microvascular Invasion in Small Hepatocellular Carcinoma. Issue 4 (July 2016) - Kobayashi, Tomoki; Aikata, Hiroshi; Honda, Fumi; Nakano, Norihito; Nakamura, Yuki; Hatooka, Masahiro; Morio, Kei; Morio, Reona; Fukuhara, Takayuki; Masaki, Keiichi; Nagaoki, Yuko; Kawaoka, Tomokazu; et al.
Abstract : Objectives: This study aimed to assess the value of preoperative fluorine 18 fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET-CT) for predicting microvascular invasion (MVI) in small hepatocellular carcinoma (HCC). Methods: We retrospectively examined 60 patients who received 18 F-FDG PET-CT prior to hepatic resection for small HCC (⩽30 mm) with subsequent MVI confirmation by histopathology. The associations between PET-positive status and tumor factors were assessed. Furthermore, independent predictors for MVI and diagnostic utility of each MVI predictor were assessed. Results: Multivariate analysis revealed the presence of MVI as an independent predictor of PET-positive status ( P = 0.023). Maximum standardized uptake value (SUVmax ) of 3.2 or greater ( P = 0.017) and lens culinaris agglutinin a-reactive α-fetoprotein (AFP-L3) 19% or greater ( P = 0.010) were independent predictors of MVI. Areas under the receiver operating characteristic curves for SUVmax of 3.2 or greater, AFP-L3 19% or greater, and both factors combined for predicting MVI were 0.712 (0.493-0.932), 0.755 (0.563-0.947), and 0.856 (0.721-0.991), respectively. The sensitivity and specificity for predicting MVI were 77.8% and 74.5% for SUVmax of 3.2 or greater, 66.7% and 84.3% for AFP-L3 19% or greater, and 88.9% and 82.4% for the combination. Conclusions: 18 F-FDG PET-CT and AFP-L3 may be useful for predicting MVI in small HCC, and the combination of the 2 factors provided reliable assessment for selection of suitable hepatic resection and liver transplantation candidates.